Big Five Personality Traits, Financial Literacy and Investment Decision - Thapa, Ashish (Journal of Nepalese Management and Research, 2025)
Investment behavior is increasingly explained through behavioral finance, recognizing that personality traits and financial literacy significantly shape investor decisions beyond rational models. In developing markets like Nepal, where financial education is limited and market participation is evolving, understanding how these psychological and cognitive factors interact is essential for promoting informed and sustainable investment behavior. This study analyses how retail investors in the Nepalese Stock Market are influenced by the Big Five Personality Traits, with specific focus on Surkhet district. Also, this research assesses whether financial literacy serves as a moderator for these relationships and addresses an important gap in the behavioral finance literature in emerging markets. A descriptive and causal-comparative research design was applied in this study, whereby a structured questionnaire was provided to 400 retail investors actively participating in the Nepal Stock Exchange (NEPSE) who were ‘convenience sampled’ from Surkhet District. The data was analysed with Structural Equation Modelling (SEM) using Smart PLS software to determine the direct effects as well as the moderating effects of the trait and the moderating variable. Results indicate that openness to experience; conscientiousness, agreeableness and neuroticism positively affect investment decisions; however, extraversion did not have a significant effect. Also, financial literacy strengthens the connection between openness to experience and investment decisions, thereby enhancing the predictive ability of these traits in investment decisions. This study provides valuable insight for policy makers, financial educators, and the financial advisory service industry in Nepal. Recognizing the mental aspects that affect the behavior of investors, it is possible to create specially designed financial literacy programs and advisory services based on personality to be a tool that individual investors use for making investment decisions that are more rational and informed.